2006
DOI: 10.1590/s0100-39842006000400009
|View full text |Cite
|
Sign up to set email alerts
|

Persistência do forame de Huschke: um estudo tomográfico

Abstract: OBJETIVO: Avaliar a persistência do forame de Huschke por meio do exame de tomografia computadorizada da região da orelha, abordando importantes aspectos clínicos da presença desse forame. MATERIAIS E MÉTODOS: Dois examinadores analisaram toda a região timpânica do osso temporal de 150 tomografias da região da orelha, bilateralmente, observando a presença ou a ausência do forame. RESULTADOS: No total, foram encontrados 17 (11,3%) pacientes com a referida anomalia anatômica, sendo que, destes, 13 (76,5%) perten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Studies using dry bones showed a prevalence that varied from 0.7% to 38.2% [12][13][14][15][16] ; and between four different CT-based (spiral or cone beam) studies, the variation of persistent FH was 4.6-22.7% 1,[16][17][18] . Additionally, Brazilian publications revealed persistent FH in 9.9% and 11.3% of the cases on cranium-and CT-based studies respectively 20,21 . Although the lower sample size in our study, the frequency of 15% was compatible with previous results in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using dry bones showed a prevalence that varied from 0.7% to 38.2% [12][13][14][15][16] ; and between four different CT-based (spiral or cone beam) studies, the variation of persistent FH was 4.6-22.7% 1,[16][17][18] . Additionally, Brazilian publications revealed persistent FH in 9.9% and 11.3% of the cases on cranium-and CT-based studies respectively 20,21 . Although the lower sample size in our study, the frequency of 15% was compatible with previous results in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…There is no indication for surgical approach on asymptomatic cases. However, for the persistent FH showing alterations, surgical closure with tragal cartilage graft as well as surgical repair with polyethylene implants, and titanium meshs via preauricular external approaches have been used with success and no expected recurrences 2,6,7,9,11,20 .…”
Section: Discussionmentioning
confidence: 99%
“…In the next developmental phase, there is an emergence of two tubercles or prominences growing one against another until becoming joined together in the first year of life. The tympanic bone presents now, as a result of the fusion of these two tubercles, an opening called foramen tympanicum or foramen de Huschke [2].…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…In symptomatic patients, one can usually observe painful foramen, temporomandibular joint pain, recurrent infections in the external auditory canal, ear buzzing, conductive auditory loss and salivary secretion into the external auditory canal [2].…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…primeiro ano de vida. O osso timpânico apresenta, como resultado da fusão desses dois tubérculos, uma abertura denominada Forame Timpânico (REIS et al, 2006).…”
Section: Introductionunclassified